Concept of Planning Development of Coastal Resort Settlements under Conditions of Complex Relief - FINOGENOV, Alexandr Ivanovich; POPOV, Aleksey Vladimirovich (Journal of Environmental Management and Tourism; Vol 10 No 1 (2019): JEMT Volume X Issue 1(33) Spring 2019DO - 10.14505//jemt.10.1(33).13, 2019)
The scientific concept of planning development of small cities and settlements located on the coast of the Crimea peninsula of the Black Sea is outlined. The relevance of the study is due to the importance of the territory in question as the All-Russian Center for Mass Recreation, Tourism and Sport. Subject : The principles of planning organization of modern urban development and objects of transport communications under conditions of complex relief on the territory of coastal settlements of Crimea (on the example of optimizing the urban planning structure of Gurzuf urban-type settlement). Purposes: Development of scientific concept in the field of urban planning reorganization of the territory of small urban coastal settlements with the formation of new centers for the public, educational, hotel and transport-communal use. Improving the structure of urban development and objects of transport infrastructure. Methods: The concept is based on a comprehensive analysis of the process of historical exploration and development of the coastal settlements’ territories of the Crimean Peninsula under the conditions of complex relief and ineffective development. The new methods of step-by-step reorganization of urban space are proposed. Results: The concept determines further practical directions in the field of design, concerning the improvement of the planning structure of buildings within the boundaries of small urban settlements in Crimea, the creation of the spatially organized structure of new urban facilities for the public, hotel-tourism, educational and transport-communal use. The new methods of step-by-step reorganization of the structure of buildings and transport communications, ensuring the availability of facilities for mass resort recreation and tourism, sustainable public and transport links, preservation of the unique ecology of the Crimean resort zone are proposed.